TEM phase analysis of NiTi shape memory alloy prepared by self-propagating high-temperature synthesis. Issue 1 (2nd January 2017) - Karlík, M.; Haušild, P.; Klementová, M.; Novák, P.; Beran, P.; Perrière, L.; Kopeček, J.
Abstract: The effect of annealing a Ni–48at.%Ti alloy prepared by self-propagation high-temperature synthesis (SHS) by means of transmission electron microscopy (TEM) was studied. The alloy in the as-sintered condition shows the presence of B2 NiTi matrix, relatively large particles (2–100 μm) of cubic NiTi2 phase and very fine densely distributed particles of rhombohedral Ni4 Ti3 phase. The phase fractions were determined by the Rietveld refinement of neutron diffraction. Twelve-hour annealing at 1000 °C leads to coarsening of Ni4 Ti3 particles. Slow furnace cooling from the annealing temperature results in a transformation of the rhombohedral Ni4 Ti3 phase to a metastable Ni3 Ti2 phase with cubic symmetry. Its particles, coherent with the B2 matrix, have the form of thin oval platelets with lenticular cross-section. The orientation relation is either cube-to-cube or [115]B2 || [111]P and (552)B2 || (121)P . An additional isothermal annealing of the water cooled samples at 720 °C for 3 and 10 h was carried out. According to the scanning and transmission electron microscopy observation of the sample annealed for 3 h, the cubic Ni3 Ti2 phase transforms to the high-temperature tetragonal Ni3 Ti2 –H variant (space group I4/mmm).